The European Union's Politics of Energy - Plekker, Pim (2008)
Energy sources like oil and gas are depleting. In the nearby future the demand for energy will only rise further. Cheap “Energy” is the fundament of a healthy economical society. Without cheap energy everything will become more expenses. The fact that “energy” is important for a country’s economy makes it not difficult to predict that having a stable energy source is of the highest importance. It can be said that due to the fact that the European Union is depending on imported energy it is vulnerable. States who supply energy could misuse there dominant position as supplier of energy by using this as a political tool to manipulate the political decision-making process of the European Union. The Russian - Ukraine conflict, where Russia shut down her gas-export to the Ukraine, and because of that, parts of Europe had to deal with a minor disruption as well, can be seen as an example how Russia uses her dominant status as gas supplier in order to manipulate foreign decision-making. It sh.